Treatment modalities of home isolated COVID-19 patients in India: Lessons learnt - Mangla A G; Bhardwaj P
This study investigated the treatment modalities that medical practitioners in India followed for home-isolated patients. The responses via web-based survey from 201 medical practitioners treating more than 11000 COVID-19 patients, fulfilling the inclusion criteria, were analysed using STATA 11. Furthermore, we have also compared the treatment modalities followed by doctors in government and private setups. Doctors from both set up recommended protein diets followed by liquids, fruits and vegetables. Interestingly, 61.1% of government doctors advised COVID-19 treatment based on symptoms alone without an RT-PCR test, in contrast to private practitioners (38.9%). Around 45% of doctors advised blood anticoagulants to their patients. Among the various drugs, oral steroids and fabiflu prescriptions were predominantly preferred by private doctors in comparison to government doctors who preferred giving antibiotics for treatment. The present study reflects the doctors' zest to contain and cure the COVID-19 disease through their best-understood management regime guided by experience and laid guidelines to deify the suddenness of this pandemic and uphold human life, yet retrospectively, usage of drugs still needs to be established in the light of science through trials and evidence.